Bolus infusion scheme for the adjustment of steady state [11C]Flumazenil levels in the grey matter and in the blood plasma for neuroreceptor imaging - Mauler, Jörg; Heinzel, Alexander; Matusch, Andreas; Herzog, Hans; Neuner, Irene; Scheins, Jürgen; Wyss, Christine; Dammers, Jürgen; Lang, Markus; Ermert, Johannes; Neumaier, Bernd; Langen, Karl-Josef; et al. (NeuroImage (Orlando, Fla.), 2020)
The use of hybrid PET/MR imaging facilitates the simultaneous investigation of challenge-related changes in ligand binding to neuroreceptors using PET, while concurrently measuring neuroactivation or blood flow with MRI. Having attained a steady state of the PET radiotracer using a bolus-infusion protocol, it is possible to observe alterations in ligand neuroreceptor binding through changes in distribution volumes. Here, we present an iterative procedure for establishing an administration scheme to obtain steady state [11C]flumazenil concentrations in grey matter in the human brain. In order to achieve a steady state in the shortest possible time, the bolus infusion ratio from a previous examination was adapted to fit the subsequent examination. 17 male volunteers were included in the study. Boli and infusions with different weightings were given to the subjects and were characterised by kbol values from 74 ​min down to 42 ​min. Metabolite analysis was used to ascertain the value of unmetabolised flumazenil in the plasma, and PET imaging was used to assess its binding in the grey matter. The flumazenil time-activity curves (TACs) in the brain were decomposed into activity contributions from pure grey and white matter and analysed for 12 ​vol of interest (VOIs). The curves highlighted a large variability in metabolic rates between the subjects, with kbol ​= ​54.3 ​min being a reliable value to provide flumazenil equilibrium conditions in the majority of the VOIs and cases. The distribution volume of flumazenil in all 12 VOIs was determined. •Iterative establishment of an administration scheme to obtain constant [11C]flumazenil concentrations in the grey matter. .•No necessity of arterial blood sampling.•Plasma metabolite analysis to ascertain the unmetabolised flumazenil. PET imaging to assess its binding in the grey matter.•The flumazenil time-activity curves in the brain were decomposed into activity contributions from pure grey / white matter.